(untitled) (Journal of Global Humanities and Social Sciences, 2024)
Driven by the global movement for gender equality, women’s participation in various fields has gradually increased. This paper describes the evolution of women’s roles and status in geopolitical organizations and their current status, and analyzes women’s participation in geopolitical organizations, their proportion and positions in leadership, and their influence in policy making. Although the status of women in these organizations has improved, they still face many challenges such as gender stereotypes and inequality. Strategies for promoting the development of women’s roles and status in geopolitical organizations include four aspects: formulating and implementing gender equality policies, promoting gender-balanced recruitment and promotion mechanisms, enhancing women’s participation in decision-making processes, and establishing women’s networks and support systems. These strategies are intended to further promote gender equality in geopolitical organizations and enhance organizational diversity and decision-making quality.